MODEL KONTROL OTOMATIS PENGAIRAN HIDROPONIK DENGAN METODE FUZZY - Prihono, Prihono; Febryanto, Indra Dwi (Heuristic, 2024)
Recently, many hydroponic farms have emerged. This is due to the increasingly limited agricultural land and also as a way to fill time during the Covid-19 pandemic. In hydroponics, the role of water as a planting medium plays a very dominant role. This is because air is a solvent for the nutrients that plants need. So air is a key factor in poverty in the Hydroponic farming system. That need to be considered when choosing water for hydroponic cultivation is that it is based on the air acidity value. The air acidity value is important as a parameter that influences plant growth in the hydroponic cultivation method. The ideal temperature value ranges between pH 5.5-6.5. In Cangkringsari Village, Sukodono District, Sidoarjo Regency, Karang Taruna Tunas Cangkring has tried to develop hydroponic farming, but because the supply of acidic air with a pH that is not ideal causes plant growth to be poor. Therefore, an automatic control model for hydroponic irrigation is needed. The method developed uses the Fuzzy method. The Fuzzy method applied functions to control the air pump automatically, so that the Arduino Uno microcontroller and the 4502c pH sensor combined can detect the pH of the nutritious air that will be given to hydroponic plants in the range of 5.5 to 6.5. The application of the Fuzzy method can be applied to drive the nutrient pump perfectly so that with its application it can maintain the air pH in the specified range.